Importance of digital marketing in Colombian universities with accredited quality: Contributions to the qualification of its use - Grillo Torres, Camilo Mauricio; Moreno López, William (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The importance of digital marketing in the competitive strategies of universities is evident, as evidenced by many institutions that, with accredited quality, operate in Colombia. In addition to highlighting this reality, this work proposes to offer guidelines that allow qualifying the use of social networks as an element for competitiveness in the market; In this perspective, the investigative process studies the implementation of marketing strategies through different social networks in ten accredited universities, to evaluate the incidence of content on its users and, based on the analysis, formulate recommendations towards its optimization.